Configuring governmentalized teachers through introspective panopticism from the Foucauldian perspective - Chiang, Tien-Hui; MacKenzie, Alison; Sude, Bilige; Zeng, Wenjing; Thurston, Allen; Fu, Shuqiong; Yao, Yiling (International journal of educational research, 2023)
•The exercise of performativity is regulated by teaching efficiency.•Self-improvement is mainly engineered by teaching efficiency.•Responsible teachers and self-improvement are strongly correlated.•Social cultures will modify the practice of neoliberal governmentality. This paper analyses how teachers contribute to a successful society through a lens of Foucauldian perspective. It uses this lens to analyse how teachers’ self-improvement through professional development in the regime of neoliberal governmentality is influenced by society, performativity and professional ‘norms’. Data is presented from 3131 teachers, based in 55 high schools in Zhejiang province China and analysed using Structural Equational Modelling to explore the relationships between these variables. Findings indicated parental attitudes, concept of responsible subjects, and teaching quality rewards significantly influenced the subjectivity-performativity association. The subjectivity-performativity association significantly influenced teacher self-improvement, both directly, and in a relationship that was mediated by teaching efficiency. These correlations intimate that introspective panopticism enshrined within teachers’ subjectivities carries performativity.